2016
DOI: 10.1128/jcm.01586-16
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Alere i and cobas Liat Influenza A and B Tests for Rapid Detection of Influenza Virus Infection

Abstract: We compared two rapid, point-of care nucleic acid amplification tests for detection of influenza A and B viruses (Alere i [Alere] and cobas Liat [Roche Diagnostics]) with the influenza A and B virus test components of the FilmArray respiratory panel (BioFire Diagnostics) using 129 respiratory specimens collected in universal viral transport medium (80 influenza A virus and 16 influenza B virus positive) from both adult and pediatric patients. The sensitivities of the Alere test were 71.3% for influenza A vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…The advantages of this system include sample processing within each cartridge, fully automated PCR and a ‘plug and play’ system, where different samples and pathogen species can be examined simultaneously. Similarly, Roche's cobas ® Liat RT‐PCR System has been used for the detection of viral RNA at the POC . This system involves bench‐top multiplex RT‐PCR analysis of, for example, nasopharyngeal swabs for respiratory pathogens.…”
Section: Translation Of Gene Expression Signatures Into Diagnostic Pmentioning
confidence: 99%
“…The advantages of this system include sample processing within each cartridge, fully automated PCR and a ‘plug and play’ system, where different samples and pathogen species can be examined simultaneously. Similarly, Roche's cobas ® Liat RT‐PCR System has been used for the detection of viral RNA at the POC . This system involves bench‐top multiplex RT‐PCR analysis of, for example, nasopharyngeal swabs for respiratory pathogens.…”
Section: Translation Of Gene Expression Signatures Into Diagnostic Pmentioning
confidence: 99%
“…A study by Binnicker et al demonstrated similar results when comparing the cobas® Liat® Influenza A/B assay to the routine RT‐PCR assay, Simplexa Flu A/B & RSV Direct, with sensitivities of 99.2% (123/124) and 100% (23/23), respectively, for influenza A and B, and a specificity of 100% for each target . A study by Chen et al comparing the cobas® Liat® Influenza A/B assay versus another multiplex RT‐PCR assay, Prodesse ProFlu+, demonstrated comparable sensitivities of 97.7% and 98.6% for influenza A and B, respectively, with specificities of 99.2% and 99.4%, respectively . A study by Nolte et al comparing the cobas® Liat® Influenza A/B versus the Film Array respiratory panel also demonstrated sensitivities of 100% and specificities of 100% for both influenza A and B viruses.…”
Section: Discussionmentioning
confidence: 92%
“…The newer mPOC tests are significantly more reliable and have the potential for improved outcomes in the POC environment [15]. However, as more mPOC options become available, it will be important for laboratories to continue to assess their performance, as not all mPOC tests may demonstrate the same sensitivity and specificity [16]. A recently published open-label, randomized, controlled trial looking at the routine use of mPOC testing of respiratory viruses in adults presenting to hospital with acute respiratory illness enrolled 720 patients (362 assigned to POC testing and 358 to routine care).…”
Section: Turnaround Time and Patient Impactmentioning
confidence: 99%